56. THE CURRENT STATUS OF TUBERCULOSIS SERVICE AVAILABILITY AND READINESS AND SOME ASSOCIATED FACTORS IN COMMUNE HEALTH STATIONS IN NGHE AN PROVINCE, 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the current status of tuberculosis service availability and readiness and some associated factors in commune health stations, Nghe An province in 2023.Subject and methods: A cross-sectional descriptive was conducted on 401 out of 460 commune health stations in Nghe An province.Results: The results of the study showed that more than 90% of the commune health stations participating in the study were in the countryside (57.61%) and the mountainous (32.34%). Only 74.12% of the commune health stations had doctors and 39.65% had tuberculosis diagnosis, while the most common diagnosis method in commune health stations in Nghe An province is clinical signs observation (98.74%). The medicine availability in 3 areas was low and the differences between the areas were statistically insignificant.Conclusions: There are some limits in workforce, diagnosis, treatment, facilities, biological products and medicines in the current status of tuberculosis service availability and readiness.
Keywords: Service availability and readiness; tuberculosis intervention; commune health stations; Nghe An